The Impact of Artificial Intelligence on Today’s Student Life - Yosafat Tumiwa; Dave Christyfo Badasi; Artika Wulan Batas; Julio Elias Manek; Shefriano Clery Tumembow; Deitje Sofie Pongoh (Jurnal Syntax Admiration, 2024)
AI has profoundly impacted the lives of students by transforming various aspects of their education and daily activities. AI can be a very useful learning tool in a variety of contexts. Students can access learning materials tailored to their needs and learning styles, resulting in more effective learning. AI also speeds up evaluation and scoring. However, there are also issues to contend with, such as the dangers of relying on technology, problems with data privacy, and the possibility of a decline in social interaction. This article discusses the impact of AI on college students and its implications for the future of higher education. The rapid development of technology has made the emergence of the millennial era where technology has become the need of every individual, especially youth and women in the millennial era who are faced with technological advancements, so it is required to always sort out every information obtained, in order to prevent the occurrence of bad impacts because access between the worlds is easy to obtain so that it can be a weapon for irresponsible people to attack an area from the next generation. The purpose of this study is to find out the various impacts of technological developments.